1996
DOI: 10.1021/cm9505759
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Poly(arylene cobaltacyclopentadienylene)s, a New Class of Organometallic π-Conjugated Polymers, by Metallacycling Polymerization and Their Physical Properties

Abstract: Reaction of Cp‘Co(PPh3)2, where Cp‘ = η5-cyclopentadienyl (Cp) or η5-n-hexylcyclopentadienyl (hexCp), with conjugated diacetylenes, RC⋮CAC⋮CR, where A = p-phenylene, p-fluorophenylene, p-2,5-difluorophenylene, or 4,4‘-biphenylene and R = H or Me affords new organometallic polymers, [−C4R2{CoCp‘(PPh3)}−A−] n (1−6) involving linearly π-conjugated chains. The polymers are insoluble when Cp‘ = Cp but soluble in common organic solvents when Cp‘ = hexCp. It is suggested by the results of reactions of (hexCp)Co(PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…These results are similar to those for previously reported cobaltacyclopentadiene complexes with no halide groups. 2,4,11, 12 The E ЊЈ value and the reversibility of the oxidation reaction of the polymer were almost consistent with those of oligomers [Fig. 4(b), (c)].…”
Section: Electrochemistry Of Cobaltacyclopentadiene Complexessupporting
confidence: 74%
“…These results are similar to those for previously reported cobaltacyclopentadiene complexes with no halide groups. 2,4,11, 12 The E ЊЈ value and the reversibility of the oxidation reaction of the polymer were almost consistent with those of oligomers [Fig. 4(b), (c)].…”
Section: Electrochemistry Of Cobaltacyclopentadiene Complexessupporting
confidence: 74%
“…The only other example of this type of compound is an osmium complex, formed by reaction of [Os(en) 2 (H 2 O)(H 2 )] with 2,4-hexadiyne, producing the 2,5-diethynylmetallacycle exclusively [83]. [86,87] and "ZrCp 2 " [88].…”
Section: Reductive Coupling Of Buta-13-diynesmentioning
confidence: 99%
“…Nishihara and co-workers were the first group to prepare and characterize polymers of this type, successfully isolating a number of poly(arylene cobaltacyclopentadienylene)s [87]. They found that use of Cp as a ligand on Co resulted in insoluble polymers.…”
Section: Metallacyclopentadiene-containing Polymersmentioning
confidence: 99%
“…Polymers containing cobaltacyclopentadiene groups in their backbones have also been prepared via metallacycling polymerization reactions. [285][286][287][288]335,336] 8 Metal-Metal Bonded Systems Puddephatt and coworkers have reported the reaction of a platinum complex with diacetylides and diisocyanides to produce oligomers and polymers containing Pt-Pt bonds in their backbones. [337] While reactions with acetylides produced oligomers with low solubility, the IR spectra of the polymers shown in Scheme 76 did not show the presence of uncoordinated isocyanide groups.…”
Section: Metallacyclopentadienesmentioning
confidence: 99%